2015
DOI: 10.3390/met5021112
|View full text |Cite
|
Sign up to set email alerts
|

Study on Dual Modification of Al-17%Si Alloys by Structural Heredity

Abstract: Abstract:In this study, Al-17%Si alloys were dual modified by fine-grained structural materials (FSM) according to structural heredity. Microstructure and thermal analyses were undertaken to study the modification effect of the FSM master alloy on primary and eutectic Si. Primary Si is refined to a smaller size and eutectic Si is modified from needle-like to fibrous shape after FSM master alloy addition. The optimal content of FSM master alloy is 20% and the holding time is 15min. Finer FSM master alloy leads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
(24 reference statements)
0
1
0
2
Order By: Relevance
“…Rare earth (RE) elements and mischmetal (mixture of RE elements) were also reported to cause modification in both hypo- and hypereutectic Al-Si alloys [ 12 , 13 , 14 , 15 , 16 , 17 ]. It was found that the modification efficiency of 1.0 wt % La in the microstructures and mechanical properties of A356 alloy is similar to that of 0.01 wt % Sr [ 12 ]. Li et al [ 13 ] indicated that the addition of 1.0 wt % La or 1.0 wt % Ce to Al-11.7%Si-1.8%Cu alloy could refine the Si particles, but without any obvious modification effect.…”
Section: Introductionmentioning
confidence: 99%
“…Rare earth (RE) elements and mischmetal (mixture of RE elements) were also reported to cause modification in both hypo- and hypereutectic Al-Si alloys [ 12 , 13 , 14 , 15 , 16 , 17 ]. It was found that the modification efficiency of 1.0 wt % La in the microstructures and mechanical properties of A356 alloy is similar to that of 0.01 wt % Sr [ 12 ]. Li et al [ 13 ] indicated that the addition of 1.0 wt % La or 1.0 wt % Ce to Al-11.7%Si-1.8%Cu alloy could refine the Si particles, but without any obvious modification effect.…”
Section: Introductionmentioning
confidence: 99%
“…Измельчение основных фаз (дендритов алюминия, эвтектики) способствует снижению газоусадочной пористости промышленных силуминов [11,13]. В работе [14] установлено, что модифицирование заэвтектического силумина Al-17% 1 Si с позиции явления структурной наследственности добавками мелкокристаллических модификаторов способствует формированию компактных кристаллов первичного кремния блочной морфологии и мелкодисперсного эвтектического кремния.…”
Section: Introductionunclassified
“…Действенный метод улучшения их структуры и свойств -модификация многокомпонентными составами. Это позволяет воздействовать не только на кремний, входящий в состав эвтектики (α+Si), но и на кристаллы первичного кремния [9][10]. Отметим необходимость эффективно бороться с таким недостатком сплавов Al-Si-Mg, как газопоглощение.…”
unclassified